Motor Skills Development: Peculiarities of Programmed Teaching of Acrobatic Exercises to Girls Aged 15 - Alina Shueva; Olha Ivashchenko; Wladyslaw Jagiello (OVS LLC, 2021)
The purpose of the study was to determine the peculiarities of programmed teaching of a cartwheel to girls aged 15. Material and methods. The study participants were 20 girls aged 15. The children and their parents were fully informed about all the features of the study and gave their consent to participate in the experiment. To solve the tasks set, the following research methods were used: study and analysis of scientific and methodological literature; pedagogical observation, timing of training tasks; pedagogical experiment, methods of mathematical statistics, factor analysis, nearest neighbor analysis. Results. The analysis of similarities revealed that the program components are interrelated. Series of training tasks ІV, V and VI have the highest correlation. Series of training tasks І, ІІІ and IV are combined into one group and provide conditions for teaching girls aged 15 the cartwheel. Conclusions. The study obtained factor models of the teaching program, which explain 70.645% and 68.468% of the variation of results. The models characterize the two-factor structure of the teaching program where training tasks are closely connected with one another, which indicates their effective selection. It was found that the tasks of series I, II and III, and the tasks of series III, IV and V are most connected with one another, which confirms the combined nature of the method of algorithmic instructions. Optimization of the number of repetitions of the entire exercise (series of tasks VI) depends on the amount of exercises of the second and fifth series of training tasks.